Tanggung Jawab Hukum Perjanjian Asuransi Jiwa Unit Link di PT. Prudential Life Assurance Jakarta - Christine Magdalena Kurniasih Sena; Suherman Suherman (Universitas Batanghari Jambi, 2021)
This study aims to determine and understand how the legal liability of the Prudential Life Assurance Company in carrying out and marketing unit-linked life insurance products, namely insurance products that are linked to investment according to the prevailing laws and regulations. In addition, this study also aims to determine how the responsibility of agent who act for and on behalf of the company in entering into unit-linked insurance product agreements and what risks must be borne by the insurer and the insured against the unit-linked life insurance agreement. This research uses normative legal research with a statutory approach and a conceptual approach. The result of this research is that the unit linked insurance agreement is included in the agreement in general which contains the principle of consensualism, namely the existence of a voluntary agreement in this case to enter into an insurance contract agreement between the insurer and the insured. Prudential Indonesia in marketing unit-linked life insurance products has also complied with the provisions in the Financial Services Authority Circular Letter Number /SEOJK.05/2019 concerning Insurance Products Related to Investment.